Ecotextile '98--sustainable development : proceedings of the conference Ecotextile '98, the Bolton Moat House, 7 & 8th April, 1998 - Horrocks, A. Richard (Woodhead publishing in textiles., 1999)
The edited papers which comprise this book were presented at the international conference, Ecotextile '98, which was organised jointly by Bolton Institute and the British Textile Technology Group.